BUILDING BILINGUAL TERMINOLOGY FOR EMERGING FIELDS: TRANSLATION CHALLENGES AND SOLUTIONS - G‘afurova Nazokat Bakhriddin’s daughter (Ustozlar uchun, 2025)
Annotation: This article explores the process of building bilingual terminology in emerging fields such as information technology, ecology, genetics, and transport. It analyzes the linguistic, cultural, and practical challenges translators face when developing consistent and accurate terminology in under-resourced languages like Uzbek. By applying principles from terminology science and translation theory, including descriptive, functional, and Skopos-based approaches, the paper outlines key strategies for term formation, standardization, and localization. Real examples from IT, genetic engineering, and green transport illustrate both successful practices and common pitfalls. Recommendations for institutional collaboration, digital termbase development, and translator training are also provided.